The effects of non-nutritive sweeteners on energy and macronutrients intake in adults: a grade-assessed systematic review and meta-analyses of randomized controlled trials - Rostampour, Kimia; Moghtaderi, Fatemeh; Najafi, AmirHossein; Seyedjafari, Behnaz; Salehi-Abargouei, Amin (Frontiers in Nutrition, 2024)
Objectives The effect of non-nutritive sweeteners (NNSs) on long-term satiety is not well understood. This systematic review and meta-analysis were performed to investigate the effect of NNSs on long-term total energy and macronutrients intake. Methods Online databases including Scopus, PubMed, ISI Web of Science, and Google Scholar were searched up to September 2024 to find relevant randomized control trials (RCTs). A random effects model was used for estimating the overall effects. Results The results showed a reducing effect of NNSs consumption vs. sugar on total energy intake [total energy intake change = −175.26 kcal/day, 95% confidence interval (CI): −296.47 to −54.06, I2 = 61.19%] and carbohydrate intake [Hedges’ g = −0.35, 95% CI: −0.63 to −0.06, I2 = 58.99%]. While, NNSs intake vs. water was not associated with significant change in total energy intake [total energy intake change = 29.94 kcal/day, 95% CI: −70.37 to 130.24, I2 = 34.98%] and carbohydrate intake [Hedges’ g = 0.28, 95% CI: −0.02 to 0.58, I2 = 65.26%]. The Consumption of NNSs compared to the either sugar or water did not have a significant effect on fat intake [Hedges’ g sugar = 0.08, 95% CI: −0.10 to 0.26, I2 = 8.73%/ fat intake change water = 0.20 g/day, 95% CI: −3.48 to 3.88, I2 = 0%] and Protein intake [Hedges’ g sugar = 0.16, 95% CI: −0.11 to 0.42, I2 = 50.83%/Hedges’ g water = 0.00, 95% CI: −0.15 to 0.16, I2 = 0%]. Conclusion In summary, our findings suggest that NNSs consumption may be effective in reducing total energy and carbohydrate intake compared to sugar. Systematic Review Registration https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=432816, CRD42023432816.